Sex offender legislation and social control: an examination of sex offenders’ expectations prior to release - Winters, Georgia M. (Criminal justice studies, 2017)
Although there has been considerable study of desistance from criminal offending in general, very little of this research has focused on sex offenders specifically. Given the increasing number of restrictive legislations targeting sex offenders which can serve as formal social controls, it is important to understand the impact of these laws on the desistance process. A sample of 84 sex offenders who were within three months of release from prison were interviewed to determine what they knew about the laws they would be subject to upon release, their expectation for barriers to reintegration, and the extent to which they were prepared to overcome these barriers. More than one third of sex offenders who were nearing release did not know or were unsure whether they would be subject to sex offender laws upon release. Further, the majority of the sex offenders reported that they felt very or mostly prepared for reintegration. Finally, while most of the sex offenders reported anticipating some barriers to reintegration, such as difficulty finding work or housing, they did not report concerns that sex offender legislation would affect the formation of these social bonds. These findings are discussed as they pertain to the effects of sex offender legislation on the desistance process.